Comparison of water-based and in-feed antimicrobials for growth performance enhancement of weanling pigs - Gottlob, R.O.; Hastad, C.W.; Groesbeck, C.N.; Neill, C.R.; Schneider, J.D.; Frantz, N.Z.; Tokach, Michael D.; Goodband, Robert D.; DeRouchey, Joel M.; Nelssen, Jim L.; Dritz, Steven S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2009)
A total of 350 weanling pigs (initially 13.0 lb and 14 ± 3 d of age, PIC) were used to determine the effects of water-based antimicrobial on nursery pig growth performance. Pigs were given one of 5 experimental treatments: negative control (no antibiotics in the feed or water), positive control diet containing Neo- Terramycin® (140 g/ton Neomycin sulfate, 140 g/ton Oxytetracycline HCl), Neomycin sulfate in the water (24.2 mg of Neomycin sulfate per L), Oxytetracycline in the water (24.2 mg of Oxytetracycline per L), and Neomycin sulfate and Oxytetracycline (Neo/oxy) in the water. Overall (d 0 to 28 after weaning), pigs provided a water antimicrobial had greater ADG (P<0.01) and ADFI (P<0.02) than did pigs provided non-medicated water and feed. But pigs fed diets containing Neo- Terramycin® had greater ADG and ADFI (P<0.01) than did pigs provided a water antimicrobial. Pigs provided water containing Neomycin sulfate or Neo/oxy had greater ADG and ADFI (P<0.05) than did pigs provided non-medicated feed and water, and ADG and ADFI of pigs provided water containing Oxytetracycline were intermediate. There were no differences in growth performance between water antimicrobials and no differences in F/G for all treatments.
Swine research, 2005 is known as Swine day, 2005
Keywords: Swine; Nursery pig; Antibiotics; Water; Growth